2021
DOI: 10.1021/acschembio.0c00983
|View full text |Cite
|
Sign up to set email alerts
|

Making the Enterobacterial Common Antigen Glycan and Measuring Its Substrate Sequestration

Abstract: The enterobacterial common antigen (ECA), a three-sugar repeat unit polysaccharide produced by Enterobacteriaceae family members, impacts bacterial outer membrane permeability, and its biosynthesis affects the glycan landscape of the organism. ECA synthesis impacts the production of other polysaccharides by reducing the availability of shared substrates, the most notable of which is the 55-carbon polyisoprenoid bactoprenyl phosphate (BP), which serves as a carrier for the production of numerous bacterial glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…A number of studies have shown that disruption of intermediate steps in ECA biogenesis leads to isoprenoid carrier stress and peptidoglycan synthesis defects due to the accumulation of ECA synthesis intermediates on Und-P ( 26 30 ). In fact, a recent study has biochemically confirmed the accumulation of these intermediates ( 25 ). Similar defects have been observed with the disruption of O-antigen or colanic acid biosynthesis ( 60 , 83 ).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…A number of studies have shown that disruption of intermediate steps in ECA biogenesis leads to isoprenoid carrier stress and peptidoglycan synthesis defects due to the accumulation of ECA synthesis intermediates on Und-P ( 26 30 ). In fact, a recent study has biochemically confirmed the accumulation of these intermediates ( 25 ). Similar defects have been observed with the disruption of O-antigen or colanic acid biosynthesis ( 60 , 83 ).…”
Section: Discussionmentioning
confidence: 94%
“…The ECA and peptidoglycan pathways compete for Und-P and UDP-GlcNAc as depicted in Fig. S1 in the supplemental material ( 25 , 60 , 61 ). Although deletion of wecA causes generally mild phenotypes, deletion of later genes in ECA biosynthesis (e.g., wecB , wecG , wecF , or wzxE ) causes the accumulation of ECA intermediates sequestering Und-P, disrupting peptidoglycan biosynthesis and resulting in increased permeability defects, cell shape defects, and envelope stress response activation ( 26 30 , 62 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations